South Africa Digital Economy Diagnostic - World Bank Group (World Bank, Washington, DC, 2020)
South Africa is one of the digital economy leaders on the African continent, but lags developed countries. In this context, the digital economy for Africa targets appear within reach for South Africa, although efforts need to be maintained. Launched in 2018 through a collaboration between the African Union (AU) and the World Bank, the digital economy for Africa initiative aims to ensure that every individual, business, and government in Africa will be digitally enabled by 2030. South Africa can also play a leading role for regional digital development, particularly within the context of the recently signed continental free trade area (CFTA) agreement, as well closer to home in the Southern Africa development community (SADC) and common market for Eastern and Southern Africa (COMESA) context, following on the East Africa single digital market as an example. South Africa can assist by leading the agenda to harmonize customs, disseminating best practices to other countries around issues such as data regulation, improvement in the ecommerce environment, promotion of Africa wide payment systems, and the provision of an even stronger regional hub for tech entrepreneurs. In this context, the South African government is aiming to pass several reforms across core elements of the digital economy, recognizing the need for new policy directions and preparing for the fourth industrial revolution (4iR). While South Africa’s wealthy households have broad access to quality and relatively affordable internet, people earning less than South African rand (ZAR) 7000 a month are largely unconnected. This report reviews how the digital divide affects the foundations of the digital economy and provides policy options for bridging the divide. This report will provide a diagnostic and offer recommendations on the five foundations of the digital economy in South Africa. The report will examine challenges concerning digital infrastructure, public digital government platforms, digital financial services, digital entrepreneurship, and digital skills.